An Analysis of Factors that Affect CO2 Emissions in 5 ASEAN Country in 2011-2018 - Hariani, Ermatry; Febriyastuti W, Retno; Tamonsang , Matheous (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
Changes in the quality of the environment at this time until the next few years need to be considered. Changes in the quality of the environment are caused by the various activities of the economy that do humans. This change in environmental quality is represented by the variable emission of carbon dioxide (CO2) gas. This research aims to analyze the effect of the growth of the economy, city population, and the import and export of technology high on the emissions of gas carbon dioxide (CO2) in the five countries of ASEAN (Indonesia, Myanmar, Malaysia, Thailand, Vietnam) during 2011-2018. This study uses panel data (time series and cross-section). In using the method of regression of panel data is performed by Chow test and Hausman test, and elected, namely the fixed effect model. Furthermore, the classical assumption test was carried out on the selected model, including the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Results of the study are to prove that the only variable city population affects positively and significantly emissions of gas carbon dioxide (CO2). While variable independent more like a growth economy, import and export of high technology do not affect significantly emissions of gas carbon dioxide (CO2).